2014
DOI: 10.1097/ana.0000000000000016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mild Hypothermic Cardiopulmonary Bypass on the Amplitude of Somatosensory-evoked Potentials

Abstract: The increased amplitude in particularly of cortical SSEPs (N20/P25), detected specifically during steady-state hypothermia, seems to support the clinical utility of this methodology in monitoring the brain function not only during cardiac surgery with CPB, but also in other settings like therapeutic hypothermia procedures in an intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Preservation of cortical synaptic transmission is the most critical factor in early recovery; however, specificity is not high (73 % for consciousness and 75 % for CPC), probably because of brain ischemia rather than TTM or sedation, based on early (33 h from CA) recordings [ 9 , 10 , 13 , 15 ]. Indeed, our data showed that TTM (33–34 °C) and sedation did not change EEG and SSEP at all, reinforcing the fact that the greatest determinant of brain dysfunction both in intensive care [ 47 ] and in the operating room [ 48 ] is brain ischemia. Moreover, hypnotic sedation (e.g., midazolam and propofol) does not attenuate pain-related ML-SSEPs (like opioids do), as ML-SSEPs seem to be the neurophysiological expression of the activation of the brain-area network involved both in pain perception [ 11 , 32 ] and other salient sensory input [ 33 ].…”
Section: Discussionsupporting
confidence: 65%
“…Preservation of cortical synaptic transmission is the most critical factor in early recovery; however, specificity is not high (73 % for consciousness and 75 % for CPC), probably because of brain ischemia rather than TTM or sedation, based on early (33 h from CA) recordings [ 9 , 10 , 13 , 15 ]. Indeed, our data showed that TTM (33–34 °C) and sedation did not change EEG and SSEP at all, reinforcing the fact that the greatest determinant of brain dysfunction both in intensive care [ 47 ] and in the operating room [ 48 ] is brain ischemia. Moreover, hypnotic sedation (e.g., midazolam and propofol) does not attenuate pain-related ML-SSEPs (like opioids do), as ML-SSEPs seem to be the neurophysiological expression of the activation of the brain-area network involved both in pain perception [ 11 , 32 ] and other salient sensory input [ 33 ].…”
Section: Discussionsupporting
confidence: 65%
“…Post-cardiac arrest and moribund patients, patients in whom cerebral death was suspected or for whom withdrawal of life-sustaining therapies had been decided, and patients suffering from preexisting of acquired neuropathies were not included. Hypothermia may influence evoked potentials’ conduction times [3033]. To avoid any confounding effect related to temperature, no evoked potential was recorded while body temperature was below 35 °C.…”
Section: Methodsmentioning
confidence: 99%